Automatic J–A Model Parameter Tuning Algorithm for High Accuracy Inrush Current Simulation - Wen, Xishan; Zhang, Jingzhuo; Lu, Hailiang (Energies (Basel), 2017)
Inrush current simulation plays an important role in many tasks of the power system, such as power transformer protection. However, the accuracy of the inrush current simulation can hardly be ensured. In this paper, a Jiles–Atherton (J–A) theory based model is proposed to simulate the inrush current of power transformers. The characteristics of the inrush current curve are analyzed and results show that the entire inrush current curve can be well featured by the crest value of the first two cycles. With comprehensive consideration of both of the features of the inrush current curve and the J–A parameters, an automatic J–A parameter estimation algorithm is proposed. The proposed algorithm can obtain more reasonable J–A parameters, which improve the accuracy of simulation. Experimental results have verified the efficiency of the proposed algorithm.